Epidemiology and characteristics of childhood glaucoma: results from the Dallas Glaucoma Registry - Fung DS (Dove Medical Press, 2013)
Derrick S Fung, M Allison Roensch, Karanjit S Kooner, H Dwight Cavanagh, Jess T WhitsonDepartment of Ophthalmology, University of Texas Southwestern Medical Center, Dallas, TX, USAPurpose: Few studies have provided epidemiological characteristics of childhood glaucoma in a large, multiethnic population. This information is important if we are to better screen for and characterize this specific type of glaucoma. In this study, we evaluate the characteristics of patients with childhood glaucoma, including glaucoma suspects, as identified through the Dallas Glaucoma Registry (DGR).Patients and methods: The DGR catalogs the characteristics of glaucoma patients seen at University of Texas Southwestern Medical Center, an academic tertiary referral center for a large, multiethnic, urban population in the United States. We analyzed these patients with respect to race, medical and surgical treatment, cup-to-disc ratio, intraocular pressure, and visual outcomes.Results: The study comprised 376 eyes of 239 childhood glaucoma patients, of whom 19% had primary congenital glaucoma, 4% had primary juvenile glaucoma, 45% had secondary glaucoma, and 31% were glaucoma suspects. Trauma and postsurgical aphakia were the most common causes for secondary glaucoma. Thirty-eight percent of patients were Hispanic, 30% were Caucasian, 21% were African American, 3% were Asian, and 9% were unknown or unreported. Male sex was more common at 56%. Of all eyes with glaucoma, 65% received surgical intervention while 70% required at least one medication for intraocular pressure control. Trabeculotomy and tube-shunt surgery were the most common surgeries performed. Of patients who could have Snellen visual acuity measured, glaucoma suspect eyes had the largest proportion of eyes (96%) with good visual acuity (better than 20/40) while primary congenital glaucoma eyes had the smallest proportion (41%) with good visual acuity. Secondary glaucoma eyes had the largest proportion of eyes (30%) with poor visual acuity (worse than count fingers).Conclusion: The most common etiologies of childhood glaucoma were primary congenital glaucoma and secondary causes including trauma and postsurgical aphakia. A high proportion of glaucoma patients were of Hispanic background, reflecting the patient population studied. Trabeculotomy and tube-shunt surgery were the most common surgical interventions performed.Keywords: congenital glaucoma, childhood glaucoma, epidemiology, characteristics